The Role of Stellate Cells in Pancreatic Ductal Adenocarcinoma: Targeting Perspectives - Wu, Yang; Zhang, Chun; Jiang, Kuirong; Werner, Jens; Bazhin, Alexandr V.; D’Haese, Jan G. (Frontiers in Oncology, 2021)
Pancreatic ductal adenocarcinoma (PDAC) is a gastrointestinal malignancy with a dismal clinical outcome. Accumulating evidence suggests that activated pancreatic stellate cells (PSCs), the major producers of extracellular matrix (ECM), drive the severe stromal/desmoplastic reaction in PDAC. Furthermore, the crosstalk among PSCs, pancreatic cancer cells (PCCs) as well as other stroma cells can establish a growth-supportive tumor microenvironment (TME) of PDAC, thereby enhancing tumor growth, metastasis and chemoresistance via various pathways. Recently, targeting stroma has emerged as a promising strategy for PDAC therapy, and several novel strategies have been proposed. The aim of our study is to give a profound review of the role of PSCs in PDAC progression and recent advances in stroma-targeting strategies.